Re-examining the Influence of Tax Compliance Costs on Entrepreneurial Intentions within Nigeria’s Business Landscape - Mohammed Aminu Bello (Yayasan Sinergi Kawula Muda, 2025)
This research explores how tax compliance costs affect entrepreneurial intentions in Nigeria’s business sector. It specifically evaluates the impact of monetary, time, and psychological compliance costs on individuals' propensity to engage in entrepreneurial endeavors. The moderating role of perceived government support is also assessed. Utilising a quantitative survey design, data were collected from 420 participants, with 392 valid responses analysed through descriptive, correlation, and regression methods. Findings reveal that all dimensions of tax compliance costs exert a significant negative influence on entrepreneurial intentions, while perceived government support mitigates these adverse effects. The study recommends simplifying tax procedures, minimising compliance expenses, and enhancing tax education to promote entrepreneurial activities. Implications for tax policy formulation and entrepreneurship development are also discussed.